Financial factors and the macroeconomy - Carolina Sierimo; Matti Virén (Bank of Finland, 1995)
This paper examines the relationships between financial and nonfinancial variables in three Nordic countries (Finland, Norway and Sweden).We try to find out whether there exists some kind of dichotomy between these two sets of variables, both in terms of levels of variables and the respective volatilities.In particular, we scrutinize the role of the stock market (stock prices and stock market turnover) in this respect.The analysis makes use of standard time series analytical tools, cointegration analysis, analysis of Granger causality and cross-spectral analysis.The results of these empirical analyses suggest that, although the behaviour of the financial variables has been quite similar, there are important differences between these three countries.Still, in all countries important relationships between these sets of variables are detected.However, in most cases causality seems to be bidirectional or instantaneous.
URN:NBN:fi:bof-20140807301
Keywords: 330